Tingkat Toleransi Tanaman Lamtoro mini (Desmanthus virgatus) terhadap Cekaman Salinitas melalui Teknik Kultur Jaringan: Tolerance Level of Desmanthus virgatus to Salinity Stress through Tissue Culture Techniques - Cindy Hardianti Nufus; I Prihantoro; P D M H Karti (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2022)
Desmanthus virgatus has high potential as a source of animal feed and has the opportunity to develop as forage crops in saline areas. This study aimed to obtain information on the tolerance level of D.virgatus to salinity stress at different levels using tissue culture techniques. The experimental design used was a completely randomized design (CRD) with 5 treatments and 25 replications. The treatments were P0 (NaCl 0 ppm), P1 (NaCl 2500 ppm), P2 (NaCl 5000 ppm), P3 (NaCl 7500 ppm), and P4 (NaCl 10000 ppm). The variables observed were plant height, number of compound leaves, number of leaf twigs, leaf color, leaf loss, and plant viability. The results showed that the addition of NaCl with a level of more than 2500 ppm had a significant (p<0.05) effect on plant height, number of compound leaves, number of leaf twigs, and leaf color, but had no significant effect on leaf loss and plant viability. It is concluded D.virgatus had a tolerance level of salinity stress up to 2500 ppm.